Dentists' awareness about the link between oral and systemic health - Muhammad A Nazir; Faisal Izhar; Kamal Akhtar; Khalid Almas (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Oral health is integral to systemic health. There is a growing body of evidence of an association between periodontal and systemic diseases. The aim of the study was to evaluate the awareness of dentists regarding link between oral and systemic health. MATERIALS AND METHODS: Data was collected using a self-administered pilot-tested questionnaire. Dentists awareness about link between oral and systemic link was assessed on five point likert scale. Data was entered and analysed using SPSS. RESULTS: Of the 588 dentists, 500 completed the questionnaire (response rate 85.03%). About 93% of the participants (mean age 25.82 ± 4.21 years) agreed that oral health was associated with systemic health. Most dentists were aware of a connection between periodontal disease and diabetes (84.4%) and heart disease (70.2%). Similarly, 85.6% believed in the negative impact of oral disease on the quality of life of patients. More female than male dentists were aware of the relationship between periodontal disease and adverse pregnancy outcomes, diabetes, and rheumatoid arthritis (P < 0.001). Most dentists (97%) believed that more patients would seek oral care if they were aware of the oral-systemic link. After adjustments, private dentists were 4.65 times more likely than public dentists to believe in improving access to oral care with increased patient awareness of the oral-systemic connection (P = 0.011). CONCLUSIONS: Most dentists were aware of the oral-systemic link. They believed that patients' access to oral care would improve if they were aware of a connection between oral and systemic health. Therefore, patients should be informed of the oral-systemic link to improve their oral health.